Variations in the Quality of Tuberculosis Care in Urban India : A Cross-Sectional, Standardized Patient Study in Two Cities - Kwan, Ada; Daniels, Benjamin; Saria, Vaibhav; Satyanarayana, Srinath; Subbaraman, Ramnath; McDowell, Andrew; Bergkvist, Sofi; Das, Ranendra K.; Das, Veena; Das, Jishnu; Pai, Madhukar (PLoS, 2019)
India has the highest burden of tuberculosis (TB). Although most patients with TB in India seek care from the private sector, there is limited evidence on quality of TB care or its correlates. Following our validation study on the standardized patient (SP) method for TB, we utilized SPs to examine quality of adult TB care among health providers with different qualifications in 2 Indian cities.